2022
DOI: 10.1002/ca.23896
|View full text |Cite
|
Sign up to set email alerts
|

Variations in human pulmonary vein ostia morphology: A systematic review with meta‐analysis

Abstract: This study aimed to establish the most accurate and up‐to‐date anatomical knowledge of pulmonary veins (PV), ostia variations, diameters and ostial area, to provide physicians, especially heart and thoracic surgeons with exact knowledge concerning this area. The main online medical databases, such as PubMed, Embase, Scopus, Web of Science, and Google Scholar, were searched to gather all studies in which the variations, maximal diameter, and ostial area of the PVs were investigated. During the study, the prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 139 publications
0
5
0
Order By: Relevance
“…Existing studies have not considered area of PVs while assessing stroke risk for AF patients. Previously, Bonczar suggested that left sided PVs have smaller ostia than the corresponding right-sided PVs, and the inferior PVs ostia are smaller than the superior by meta-analysis [ 35 ]. Also, they found that the left common PV ostium size is the largest among all veins analyzed, while the right middle PV ostium is the smallest.…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies have not considered area of PVs while assessing stroke risk for AF patients. Previously, Bonczar suggested that left sided PVs have smaller ostia than the corresponding right-sided PVs, and the inferior PVs ostia are smaller than the superior by meta-analysis [ 35 ]. Also, they found that the left common PV ostium size is the largest among all veins analyzed, while the right middle PV ostium is the smallest.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of such anatomical variations can eliminate potential risks while simultaneously aiding in the successful performance of arrhythmia treatments and invasive cardiothoracic procedures (Bonczar, Piątek‐Koziej, et al, 2022; Kuniewicz et al, 2022). This can prevent any dissection and permanent damage to the AVNA and the arterial network of the conduction axis.…”
Section: Discussionmentioning
confidence: 99%
“…However, the diameter of LIPV decreases as it approaches the LA (Kim et al, 2005). Moreover, the inferior PVs are smaller than the superior PVs (Bonczar et al, 2022). Our study's embryonic and fetal specimens showed a similar trend to the adult morphology in that the proximal cross‐section of the left PVs is flatter and smaller than that of the right PVs.…”
Section: Discussionmentioning
confidence: 99%